Regret Now, Compensate It Later: The Benefits of Experienced Regret on Future Altruism - Lu, Teng; Liang, Dapeng; Hong, Mei; Sun, Jiayin (Frontiers in Psychology, 2022)
Abstract: This article explores how experienced regret and relief evoked in a risky gambling task influence subsequent intertemporal pro-social behavior. We apply a dictator game experiment with delayed rewards to investigate the effect on donating behavior by simultaneously the time delay when the recipient accepts the donation and the emotions experienced by the participant. We examine this effect using a choice titration procedure. The results reveal that independent of the prior experienced emotions, participants’ donations decrease as the time delay rises; the hyperbolic model provides a better explanation of this finding. Significantly, experienced regret impacts the shape of the social discount function with delayed rewards, which is reflected in notably different discount rates. Participants who experienced regret exhibit a lower discount rate than those in the relief condition. Note that this distinct type of generosity differs significantly at the 14-day delay but not at the shortest and longest. It follows that regret can promote future altruism and intertemporal pro-social behavior, depending on the delay.